Donald Friede papers - Friede, Donald; Friede, Eleanor
Correspondence, manuscripts of published and unpublished writings, reports, diaries, biographical materials, photographs, and other papers pertaining primarily to Friede's career in publishing. Documents his association as literary agent and publisher with a number of prominent authors including Ludwig Bemelmans, Theodore Dreiser, Richard Gump, Ernest Hemingway, MacKinlay Kantor, and Giorgio Lolli. Includes notes by Friede's wife, Eleanor, relating to the materials in the collection.
Microfilm edition of correspondence between Ernest Hemingway and Friede available
Microfilm of originals in private hands.
Private
Literary agent and publisher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bemelmans, Ludwig, -- 1898-1962.; Dreiser, Theodore, -- 1871-1945.; Gump, Richard, -- 1906-; Hemingway, Ernest, -- 1899-1961.; Kantor, MacKinlay, -- 1904-1977.; Lolli, Giorgio, -- 1905-1979.; Authors and publishers; Publishers and publishing -- United States; Literary agents; Publishers